Efektivitas Desain Didaktis Materi Lingkaran Berbasis Realistic Mathematics Education terhadap Kemampuan Pemahaman Konsep Matematis - Ellis Salsabila; Mimi Nur Hajizah; Pinta Deniyanti Sampoerno (Jurnal Riset Pendidikan Matematika Jakarta, 2025)
This study aims to examine the effectiveness of a didactical design-based teaching material grounded in Realistic Mathematics Education (RME) on the topic of circles in improving students’ conceptual understanding of mathematics. The study employed a quasi-experimental approach with a nonequivalent control group design. The participants consisted of 60 eighth-grade students from a junior high school, divided into the experimental group using RME-based learning modules and the control group receiving conventional, teacher-centered instruction. The main instrument was a conceptual understanding test developed based on six indicators: restating concepts, providing examples and non-examples, classifying, representing, explaining relationships among concepts, and applying procedures meaningfully. Results revealed that the experimental group achieved a higher mean N-gain (0.74, high category) compared to the control group (0.30, low–moderate category). The t-test showed a significant difference (p < 0.001) with a large effect size (Cohen’s d = 1.47). Analysis by indicator indicated significant improvements across all aspects, particularly in explaining conceptual relationships and mathematical representation. These findings confirm that RME-based didactical design materials effectively enhance students’ conceptual understanding of circles by facilitating meaningful rediscovery through real-world contexts and progressive mathematical modeling. Practically, the study suggests that mathematics teachers can adopt RME designs as an alternative instructional approach to promote deeper, contextual, and communicative learning in geometry.